Effects of Plant Growth Regulators on in vitro Propagation of Economically Important Ornamental Plant Rosa hybrida L. - Aggarwal, Diwakar; Upadhyay, Sushil Kumar; Kumar, Kuldeep; Sehrawat, Nirmala; Tuli, Hardeep Singh; Singh, Raj (Asian Journal of Biological and Life Sciences, 2020)
Micro propagation protocol from selected plants of Rosa hybrida using nodal segments as explant was standardized. Shoot cultures were initiated on MS medium supplemented with 6-benzyle adenine (BA, 2.5 μM). For shoot proliferation, BA and Kinetin (KIN) either alone or in combination with giberellic acid (GA3) were used. BA was found to be better for shoot proliferation and elongation as compared with KIN. Maximum shoot proliferation was observed on MS medium containing 10.0 μM BA in combination with 0.5 μM GA3. Indole 3-butyric acid (IBA) was found to be better auxin for induction of roots and maximum rooting frequency was observed on ¼ MS medium supplemented with 5.0 μM of IBA. Micro propagated plants showed 85 % survival during polyhouse and greenhouse conditions.
Keywords: Floriculture; Flowers; Garden; Micro propagation; Rose